Cd22 controls germinal center b cell receptor signaling, which influences plasma cell and memory b cell output - Meyer, Sarah Johanna; Steffensen, Marie; Acs, Andreas; Weisenburger, Thomas; Wadewitz, Charlotte; Winkler, Thomas; Nitschke, Lars (Journal of Immunology, 2021)
Germinal center reactions are established during a thymus-dependent immune response. Germinal center (GC) B cells are rapidly proliferating and undergo somatic hypermutation in Ab genes. This results in the production of high-affinity Abs and establishment of long-lived memory cells. GC B cells show lower BCR-induced signaling when compared with naive B cells, but the functional relevance is not clear. CD22 is a member of the Siglec family and functions as an inhibitory coreceptor on B cells. Interestingly, GC B cells downregulate sialic acid forms that serve as high-affinity ligands for CD22, indicating a role for CD22 ligand binding during GC responses. We studied the role of CD22 in the GC with mixed bone marrow chimeric mice and found a disadvantage of CD222/2 GC B cells during the GC reaction. Mechanistic investigations ruled out defects in dark zone/light zone distribution and affinity maturation. Rather, an increased rate of apoptosis in CD222/2 GC B cells was responsible for the disadvantage, also leading to a lower GC output in plasma cells and memory B cells. CD222/2 GC B cells showed a clearly increased calcium response upon BCR stimulation, which was almost absent in wild-type GC B cells. We conclude that the differential expression of the low-affinity cis CD22 ligands in the GC normally results in a strong attenuation of BCR signaling in GC B cells, probably due to higher CD22-BCR interactions. Therefore, attenuation of BCR signaling by CD22 is involved in GC output and B cell fate.
CRIS-Team Scopus Importer:2021-08-20

Guidelines for the use of flow cytometry and cell sorting in immunological studies (second edition) - Cossarizza, Andrea; Acs, Andreas; Adam, Dieter; Adam-Klages, Sabine; Agace, William W.; Aghaeepour, Nima; Akdis, Mübeccel; Allez, Matthieu; Almeida, Larissa Nogueira; Alvisi, Giorgia; Anderson, Graham; Andrä, Immanuel; et al. (European Journal of Immunology, 2019)
These guidelines are a consensus work of a considerable number of members of the immunology and flow cytometry community. They provide the theory and key practical aspects of flow cytometry enabling immunologists to avoid the common errors that often undermine immunological data. Notably, there are comprehensive sections of all major immune cell types with helpful Tables detailing phenotypes in murine and human cells. The latest flow cytometry techniques and applications are also described, featuring examples of the data that can be generated and, importantly, how the data can be analysed. Furthermore, there are sections detailing tips, tricks and pitfalls to avoid, all written and peer-reviewed by leading experts in the field, making this an essential research companion.
CRIS-Team Scopus Importer:2019-10-29

Role of IFN-gamma-activation of distinct tumor and stromal cell populations in colorectal carcinoma pathogenesis - Britzen-Laurent, Nathalie; Guo, Wei; Langer, Victoria; Khoziainova, Svetlana; Weisenburger, Thomas; Winkler, Thomas; Straube, Julia; Waldner, Maximilian; Becker, Christoph; Naschberger, Elisabeth; Skottke, Lisa; Tripal, Philipp; et al. (CANCER RESEARCH, 2019)
CRIS-Team WoS Importer:2019-10-22